Six milestone stations and new inscriptions discovered in the Negev along the Petra-Gaza Incense Route. (2nd July 2020) - David, Chaim Ben; Isaac, Benjamin
ABSTRACT: From 1965 to 1966 a pioneering survey was carried out by Zeev Meshel and Yoram Tsafrir along the incense route between Oboda (Avdat) and the Nabataean caravansary at Sha'ar Ramon. They noted two segments of a wide, built road, along which were 11 milestone stations: 5 on the Nafha Plateau (south of Oboda) and 6 in Makhtesh Ramon. Meshel and Tsafrir dated the road and the milestones to the Nabataean period. These two scholars noted in their survey that the two segments of the road and their milestones were about 7 km apart in the area of Mount Grafon. They surmised that these segments were linked and proposed a route for that link, although they found no ancient remains along the presumed route. During the winter of 2018 the lost section was found and six milestone stations were detected. At four of those stations we found milestones with inscriptions. These are the first dated inscriptions from the incense route in the Negev. This article presents these inscriptions and evaluates their historical implications.